Leptin, CRP, and adiponectin correlate with body fat percentage in adolescents: systematic review and meta-analysis - Rocha, Ariane Ribeiro de Freitas; Morais, Nubia de Souza de; Azevedo, Francilene Maria; Morais, Dayane de Castro; Pereira, Patrícia Feliciano; Peluzio, Maria do Carmo Gouveia; Franceschini, Sylvia do Carmo Castro; Priore, Silvia Eloiza (Frontiers in Nutrition, 2025)
IntroductionAdipose tissue is important in the secretion of inflammatory substances, and may be directly or indirectly associated to the development of cardiovascular and metabolic diseases in adolescence.ObjectiveTo evaluate whether inflammatory markers are associated to body fat percentage in adolescents.MethodologySystematic review conducted following the items of the PRISMA, and registered in PROSPERO. The descriptors adolescent, body fat distribution and cytokines were combined together in the electronic databases: Scopus, PubMed, Embase, Cochrane, Scholar Google and ProQuest, independently by two researchers, in January 2022 and atualized in November 2024. Meta-analysis of the correlation of inflammatory markers with body fat percentage was conducted using the metabin function of the meta package of the RStudio software (4.0.4).ResultsResulted in 7,592 records, of which 31 articles met the inclusion criteria and were selected for this study. Cross-sectional and prospective cohort observational studies were included. The meta-analysis included 4,682 adolescents, aged 10 to 19 years, of both sexes. The inflammatory markers leptin and C-reactive protein were positively correlated (r = 0.67; r = 0.32) and adiponectin was negatively correlated (r = −0.23) with body fat percentage in adolescents of both sexes.ConclusionIn adolescents, the body fat percentage is related to the inflammatory markers leptin, C-reactive protein and adiponectin. It is important to evaluate the body fat composition of adolescents in clinical practice to identify those with a higher percentage of fat, that may reflect an inflammatory profile, as well as increased cardiometabolic risk that accompanies adolescents into adulthood.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42020208305, identifier PROSPERO: CRD42020208305.